Physical and psychological consequences on nurses affected by workplace violence: a scoping review protocol - Sergio Rovesti; Paola Ferri; Domenico Cannizzaro; Ilaria Saguatti; Dalia Caleffi (BMJ Open)
Introduction Healthcare settings are experiencing profound changes that make them increasingly complex and demanding environments, particularly for nurses. Against this backdrop are the numerous phenomena of violence in healthcare settings, which are a worrying reflection of the growing problem of aggression in society. Institutions maintain a constant focus on the phenomenon while trying to counter it; however, workplace aggression is still on the rise.Workplace violence (WPV) potentially leads to lower quality of care and increased costs; it also exposes nurses to burnout, turnover and intention to leave the profession.The purpose of this scoping review is to explore the physical and psychological consequences on nurses who are victims of WPV and to identify possible correlations with burnout, turnover and intention to leave the workforce.Methods and analysis This scoping review will follow the methodology proposed by Arksey and O’Malley, also incorporating recommendations from the Joanna Briggs Institute Handbook for Scoping Review. A literature search will be conducted in PubMed, CINAHL, PsycInfo, Web of Science and Scopus. Grey literature sources including Google Scholar and ProQuest Dissertations & Theses will also be consulted. Data will be summarised in descriptive form and categorised according to the identified outcome variables, following an inductive approach. The results will be presented following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews guidelines.The review will include studies published from January 2020 to March 2025.Ethics and dissemination This scoping review represents the preliminary phase of a larger project aimed at developing support strategies for nurses who are victims of violence.This scoping review protocol has been registered in the Open Science Framework (https://osf.io/785qd/?view_only=21952c15efd14b34a9931f07121bf935). No ethical opinion is required, as the review does not involve direct involvement of human subjects.The findings will be disseminated through peer-reviewed publications and presentations at national and international conferences and workshops dedicated to workplace safety and nursing. In addition, the results will be shared with healthcare managers and stakeholders to inform context-specific strategies and support interventions within care settings.